The Effectiveness of the Leaflet Media on Compliance of Pregnant Women Consuming Fe Tablets at Enok Transfering Health Center - Eva Mayasari; Riska Epina Hayu (Science Midwifery, 2021)
Pregnant women with anemia would affect, physical activity, increase morbidity and mortality, especially pregnant women with severe anemias.Basically, one's compliance can be improved by providing information to the public especially Fe tablets. To provide this information, several media are needed, one of which is leaf le at. This study aims to determine the effectiveness of leaflet media on maternal compliance in consuming Fe tablets at the Enok Transfer Health Center. The population was pregnant women in the third trimester and a sample of 10 people was taken by purposive sampling. The research instrument was an observation sheet. After being given counseling with leaflets most of them were still not obedient to consume Fe tablets as much as 70.6% and those who were obedient to consume Fe tablets were 29.4 %. The bivariate results showed that the provision of counseling with leaflets was effective on maternal compliance in consuming Fe tablets at the Enok Transfer Health Center, with the Wilcoxon test obtained p. value = 0.000 <0.05. It is hoped that the Enok Transfer Community Health Center can improve services, especially in the field of care for pregnant women, by implementing counseling using leaflet media about the consumption of Fe tablets.